Synthesis, electrochemical and in-situ spectroelectrochemical properties of 1,2,4 triazole containing metallo-phthalocyanines - KOCA, ATIF (SPRINGER, 2021)
Novel 4-(5-(pyridin-3-yl)-4-p-tolyl-4H-1,2,4-triazol-3-ylthio) substituted phthalonitrile (3) and it's zinc(II) (4) and copper(II) (5) metallo-phthalocyanine derivatives were synthesized. Spectroscopic and electrochemical characterizations were performed to support the proposed structures of the complexes. Electrochemical properties of metallo-phthalocyanines were determined with cyclic and square wave voltammetry techniques and the effect of metal centers on results were investigated. It was observed that both complexes illustrated Pc based redox processes due to the redox inactivity of the metal centers. Redox assignments were supported with in-situ spectroelectrochemical measurements. Electrochemical and spectroelectrochemical responses of the complexes showed that while both complexes were aggregated in dimethyl formamide, aggregation tendency of CuPc was more than ZnPc. The in-situ spectroelectrochemical results showed that these complexes have potential to be used as electrochromic material in smart glass technologies.
Keywords: 1; 2; 4-Triazole; Phthalocyanine; Electrochemistry; Spectroelectrochemistry; SUBSTITUTED PHTHALOCYANINES; 1,2,4-TRIAZOLE; FILMS; DERIVATIVES; CORROSION; ZINC(II); COBALT